Stereocomplex Formation of High-Molecular-Weight Polylactide Using Supercritical Fluid - Purnama, Purba; Kim, Soo Hyun (AMER CHEMICAL SOC, 2010)
Stereocomplex polylactide bag been known as one of the choices to enhance the properties of polylactides. Numerous studies have been carried out on stereocomplex formation and characterizations, but these have a limitation in the case of high-molecular-weight polylactides. The stereocomplex formation of high-molecular-weight polylactides was observed by supercritical CO2 in the presence of solvent. Furthermore, the addition of solvent increased the degree of stereocomplex formation. We evaluated the degree of stereocomplex formation as a function of pressures, solvent concentration, temperature, and times. The high degree of stereocomplex formation was achieved at 30% of dichloromethane, 350 bar, and 65 degrees C. Compared with the solution casting method, stereocornplex formation by supercritical CO2-solvent had a higher degree of stereocomplex formation, and dry product was obtained in situ. Significant improvements of thermal and mechanical properties have been assessed for the stereocomplex obtained by supercritical method compared with either the solution casting method or their homopolymers.
Keywords: ENANTIOMERIC POLY(LACTIC ACID)S; POLY(D-LACTIC ACID); CARBON-DIOXIDE; PHASE-BEHAVIOR; CLOUD POINTS; POLY(L-LACTIDE); CRYSTALLIZATION; DEGRADATION; NUCLEATION; MORPHOLOGY